موقف الأمة العربية من الحرب العالمية الأولى (1914-1918م) - زيان رقية (جامعة محمد بوضياف بالمسيلة, 2025)
يتناول هذا البحث موقف الامة العربية من الحرب العالمية الأولى ، فالحرب العالمية الأولى تعتبر نقطة مفصلية في العالم ككل خاصة على العرب ، فالبعض من الولايات كان واقعا تحت سيطرة الدولة العثمانية والبعض الاخر تحت سيطرة الدول الأوروبية و قد كانت القوى الاستعمارية الأوروبية تطمع للاستيلاء على الولايات العربية ككل ، وقد تباينت مواقف العرب تجاه الحرب ، ففي المشرق تحالف الشريف حسين مع الحلفاء طمعًا في تحقيق الاستقلال، وهو ما تجسد في الثورة العربية الكبرى التي قادها الشريف حسين سنة 1916. إلا أن هذه الثورة اصطدمت بالمصالح الاستعمارية، حيث تم التآمر على تقسيم الأراضي العربية من خلال اتفاقية سايس – بيكو، كما تم التنصل من الوعود البريطانية بدعم دولة عربية مستقلة، لصالح تنفيذ وعد بلفور الذي مهّد لقيام كيان صهيوني في فلسطين. من جهة أخرى، واجهت شعوب المغرب العربي، خاصة الجزائر، الاستعمار الفرنسي الذي فرض قانون التجنيد الإجباري، مما فجّر موجة من الرفض الشعبي تجلت في المظاهرات، الهجرات الجماعية، والثورات المسلحة في بني شقران والأوراس والهقار. كما برز النشاط السياسي بقيادة الأمير خالد الذي طالب بالمساواة في الحقوق مع الفرنسيين، وأسهم في بلورة وعي سياسي جزائري مبكر. وعليه، فإن الحرب لم تكن مجرد صراع عسكري عالمي، بل كانت مرحلة حاسمة في تشكل الوعي القومي العربي، وأدت إلى ولادة حركات تحررية ستتطور لاحقًا إلى نضالات سياسية ومسلحة من أجل الاستقلال وبناء الدول الوطنية. The Summary : This research addresses the position of the Arab nation during World War I, a pivotal turning point for the entire world, particularly for the Arabs. Some Arab countries were under Ottoman control, while others were dominated by European powers, which sought to seize control of the Arab world as a whole. Arab responses to the war varied: in the East, Sharif Hussein allied with the Allied Powers in hopes of gaining independence, a vision that materialized through the Great Arab Revolt he led in 1916. However, the revolt soon clashed with colonial ambitions, as the Sykes-Picot Agreement secretly divided the Arab territories between Britain and France, and Britain reneged on its promises of supporting an independent Arab state in favor of implementing the Balfour Declaration, which paved the way for the establishment of a Zionist homeland in Palestine. Meanwhile, in the Maghreb—particularly in Algeria—the French colonial authorities imposed a compulsory conscription law, sparking widespread resistance through protests, mass emigration, and armed revolts in beni, the Aurès, and the Hoggar. Political activism also emerged, led by Emir Khaled, who demanded equal rights for Algerians and French citizens and contributed to the early development of Algerian political awareness. Thus, the war was not merely a global military conflict but a crucial phase in shaping Arab national consciousness, ultimately giving birth to liberation movements that would evolve into organized political and armed struggles for independence and the building of national states.